Locking Dorsal Plate in Four-Bone Arthrodesis in SLAC and SNAC 3 Wrist - Odella, Simona; Querenghi, Amos M.; Locatelli, Francesco M.; Dacatra, Ugo; Creta, Elia; Tos, Pierluigi (Joints, 2018)
Purpose The aim of this study was to evaluate the effectiveness and the safety of performing a four-bone arthrodesis (FBA) with dorsal locking plate in patients suffering from stage III scapholunate advanced collapse/scaphoid nonunion advance collapse (SLAC/SNAC) wrist.Methods We evaluated retrospectively 20 patients surgically treated by a FBA with the use of locking dorsal plate. All the patients were clinically evaluated at follow-up for grip strength, range of motion, and pain (visual analog scale), and with the Disability of the Arm, Shoulder and Hand score and the Mayo wrist score. Imaging evaluation was performed on standard X-rays.Results The mean follow-up was 6 years (range: 1–11 years). During follow-up, the patients showed good clinical outcomes in terms of pain relief and grip strength. Revision surgery was necessary only in one case because of screws loosening. In all cases, a solid bone fusion was achieved except in one patient, who presented a healing of lunocapitate joint. This condition did not affect the clinical outcomes.Conclusion FBA performed using a dorsal locking plate is a salvage procedure effective in treating stage III SLAC/SNAC wrist. In our study, this technique provided good clinical outcomes at mid-term follow-up with a very low complication rate.Level of Evidence Level IV, therapeutic case series.
Keywords: four-bone arthrodesis; SLAC; SNAC; wrist; locking plate